Awareness and Acceptance of Post-Partum Intrauterine Contraceptive Device Insertion (PPIUCD) among Patients Attending a Tertiary Care Hospital Karachi - Saba Pario, Ayisha Raja, Sughra Abbasi, Samina Naz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The knowledge, awareness and acceptance regarding contraceptives are variable in different parts of world. Family planning is still considered a stigma in most parts of the world. Contraceptive use for family planning is a key to understand the profound changes in fertility and to improve reproductive health worldwide. Objective: To evaluate the awareness and acceptance of the post-partum intrauterine contraceptive Device Insertion (PPIUCD) among the pregnant women visiting the Outdoor Department of Obstetrics and Gynecology in a tertiary care Hospital Malir Cantt Karachi. Study design and setting: A cross sectional study was conducted during the period January 2022- June 2022. Material and Methods: This cross sectional study was conducted at the Tertiary care Hospital, Malir cantt, Karachi, for six months from (January 2022-June 2022) Data were collected using interviewer administered structured questionnaire was filled after the informed consent. The inclusion criteria: were the women agreed to participate the study and agreed to fill the questionnaires Urdu version, who visited outdoor department. The exclusion criteria were the women who refuse to ill the questionnaire. Results: This study shows the acceptance rate of PPIUCD is 12% of 200 women who participated this study. The commonest reasons for their denial were the inadequate information or knowledge of PPIUCD. The acceptance rate of PPIUCD was associated with their awareness and the long term effectiveness. Women who have completed their secondary or higher education were more informed and accepted than uneducated women. (AOR = 3, CI = 11.81, 53.91). The age group ranging from 25-30 years showed positive acceptance for PPIUCD. Conclusion: The rate of acceptance for postpartum intrauterine contraceptive device turns out to be low in this study, though this is an effective and safe method of postpartum family planning. The perceived concerns and fears about the PPIUCD are due to lack of awareness regarding its use among women attending the antenatal clinics. Keywords: PPIUCD, Contraception, Postpartum FP, awareness.